The Use Of Environmentally Acceptable Energies (Eurasian Journal of Engineering and Technology, 2024)
This article examines the technologies for the use of solar energy, in particular, on the example of Israel. Methods for improving energy efficiency are analyzed through solar water heaters and passive heating systems. Examples of how to obtain hot water year-round through water heaters and increase the efficiency of devices are given. The importance of building structure and efficient heat saving methods are also discussed in the use of solar energy. The article reveals the importance of innovative technologies in the field of solar energy.